Molecular sieve composite material as well as preparation method and application thereof
By combining SCM-1, SCM-2 and/or SCM-6 molecular sieve with polyethyleneimine, molecular sieve composite materials are prepared, which solves the problem of poor carbon dioxide adsorption performance in the prior art, and achieves efficient carbon dioxide adsorption and selectivity.
Patent Information
- Application Number
- CN202311293174.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-08
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2043-10-08
AI Technical Summary
The prior art is difficult to payload high content of polyethyleneimine at lower temperatures, resulting in poor carbon dioxide adsorption performance.
SCM-1, SCM-2 and/or SCM-6 molecular sieves are used to combine with polyethyleneimine to prepare molecular sieve composite materials through impregnation method to improve the load capacity and molecular dispersion of polyethyleneimine.
The adsorption amount and selectivity of carbon dioxide are significantly improved, excellent carbon dioxide adsorption properties at lower temperatures are achieved, and the material is easy to operate and mold.
Smart Images

Figure CN119771362A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a molecular sieve composite material and a preparation method and application thereof, and belongs to the field of carbon dioxide gas adsorption, separation and purification. Background Art
[0002] Economic and social development has led to a continuous increase in the demand for energy in various countries. With the gradual implementation of carbon reduction and emission reduction work, however, under the current complex situation, in order to stabilize economic growth, it is necessary to ensure a safe and stable supply of energy. Therefore, it is expected that coal, oil, etc. will still be the main energy consumption in the future, so the development of carbon emission reduction technology has become an urgent need; carbon dioxide capture, utilization and storage (CCUS) as one of the solutions has attracted more and more attention from researchers and the industry. Among them, solid adsorption separation has broad development prospects as one of the important technical solutions of CCUS due to its advantages such as low regeneration energy consumption, easy equipment construction and moderate output.
[0003] Researchers have made many effective attempts to prepare solid adsorbents by loading polyethyleneimine (PEI) onto porous carriers for selective adsorption of carbon dioxide, such as mesoporous silica materials SBA-15 or MCM-41 modified with polyethyleneimine (Energy & Fuels, 2002, 16, 1463; Microporous and Mesoporous Materials, 2008, 113, 31; Journal of the American Chemical Society, 2009, 131, 5777), which can achieve excellent carbon dioxide adsorption at 75°C. However, this performance is not ideal at the actual flue gas capture temperature. The advantages of the adsorbent cannot be brought into play at 40-60°C, and the loaded amine groups are difficult to fully disperse in the mesoporous channels, so the specific surface area of the material cannot be fully utilized and the expected effect cannot be achieved. The flaky morphology and layered structure have improved this problem to a certain extent. CN104437418B discloses a layered material loaded with polyethyleneimine and a preparation method thereof. The Kenyaite layered silicate material loaded with polyethyleneimine can be prepared by a one-pot method in the presence of a silicon source, a heteroatom source and an alkaline substance. However, due to the limited synthesis conditions of the layered material, the loading amount of polyethyleneimine is not high and the molecular weight is not very large, and the improvement of carbon dioxide adsorption is limited. Therefore, it is of great positive significance to develop an adsorbent with strong selective carbon dioxide adsorption ability. Summary of the invention
[0004] In view of the shortcomings of the prior art, the present invention provides a molecular sieve composite material and its preparation method and application. The composite material of the present invention can load a high content of polyethyleneimine while still maintaining a solid state, is not only easy to operate, shape and use, but also exhibits excellent performance in the selective adsorption of carbon dioxide.
[0005] Conventional silicon-based materials (such as silicon dioxide, SBA-15, MCM-41, Kenyaite layered materials, etc.) are difficult to carry a high content of organic amines, and even if the specific surface area is high, it is difficult to show an adsorption advantage. The product is in a sticky solid state and is not easy to operate, shape and use. The inventors have found through research that SCM-1, SCM-2 and / or SCM-6 molecular sieves, due to their layered structural characteristics and the morphology of nanosheet layers, are conducive to the dispersion and exposure of polyethyleneimine, and can load a very high content of polyethyleneimine while still maintaining a solid state. They are not only easy to operate, shape and use, but also show excellent performance in the selective adsorption of carbon dioxide.
[0006] The first aspect of the present invention provides a molecular sieve composite material, comprising molecular sieve and polyethyleneimine, wherein the molecular sieve is selected from at least one of SCM-1, SCM-2, and SCM-6. Based on the weight of the composite material, the content of polyethyleneimine is 20% to 60%, and the content of the molecular sieve is 40% to 80%.
[0007] Furthermore, based on the weight of the composite material, the content of polyethyleneimine is 20% to 60%, preferably 45% to 55%, and the content of molecular sieve is 40% to 80%, preferably 45% to 55%.
[0008] Furthermore, the molecular sieve is at least one of SCM-1, SCM-2, and SCM-6, preferably at least one of SCM-1 and SCM-2. Among them, SCM-1 and SCM-2 are specifically recorded in CN104511271B, and SCM-6 is specifically recorded in CN105217651B.
[0009] Furthermore, the specific surface area of the molecular sieve is 30 to 1000 m2 / g, preferably 150 to 700 m2 / g.
[0010] Furthermore, the average molecular weight of the polyethyleneimine is 300 to 100,000, preferably 500 to 10,000.
[0011] Furthermore, the molecular sieve composite material uses the molecular sieve as a carrier, and polyethyleneimine is loaded on the carrier.
[0012] The second aspect of the present invention provides a method for preparing the above molecular sieve composite material, comprising:
[0013] (1) dissolving polyethyleneimine in a solvent to prepare an impregnation solution, and then adding a molecular sieve material for impregnation;
[0014] (2) After impregnation, the product is dried to obtain a molecular sieve composite material.
[0015] Furthermore, the molecular sieve is one or more of SCM-1, SCM-2, and SCM-6. The molecular sieve material exists in the form of, but is not limited to, the original powder obtained by direct synthesis, or the product after one-step calcination to remove the template.
[0016] Furthermore, the average molecular weight of the polyethyleneimine is 300 to 100,000, preferably 500 to 10,000.
[0017] Furthermore, the solvent used in the impregnation solution is selected from one or more of methanol, ethanol, isopropanol, butanol, cyclohexanol, acetone, water, etc., preferably at least one of methanol, ethanol and water.
[0018] Furthermore, in the impregnation solution, the mass concentration of polyethyleneimine is 0.05% to 30%, preferably 1% to 25%.
[0019] Furthermore, in step (1), the immersion temperature may be 1 to 50°C, preferably 15 to 40°C, and more preferably 20 to 30°C.
[0020] Furthermore, in step (1), the immersion time may preferably be 3 to 120 hours, more preferably 6 to 72 hours.
[0021] Furthermore, after the impregnation reaction is completed, the drying method can obtain the corresponding product by vacuum heating drying, the temperature can be 40-150°C, more preferably 50-130°C, the drying time can be 2-30h, preferably 3-24h, and the solvent extracted by vacuum extraction can be recycled and continued to be used as the solvent of the impregnation solution of the present invention.
[0022] The third aspect of the present invention provides the use of the composite material in carbon dioxide adsorption.
[0023] Furthermore, the application includes: a gas containing carbon dioxide is brought into contact with the composite material for adsorption to obtain purified gas.
[0024] Furthermore, in the carbon dioxide-containing gas, the volume content of carbon dioxide is 0.04% to 60% by volume, and other gases include at least one of nitrogen, methane, hydrogen, carbon monoxide, etc.
[0025] Furthermore, the adsorption conditions are as follows: temperature is 10-80°C, preferably 40-70°C, pressure is 0.01-100 kPa, time is 1-60 min, volume space velocity is 5-2400 h -1 .
[0026] Furthermore, the molecular sieve composite material of the present invention is used for the selective adsorption of carbon dioxide gas and can be regenerated through multiple cycles, and the regeneration conditions are: without heating or heating, the heating temperature is 40 to 150°C, preferably 60 to 130°C, using at least one of nitrogen, carbon dioxide gas, water vapor, or the tail gas after adsorption separation and purification, to purge the composite material to achieve regeneration, or to achieve regeneration by decompression degassing.
[0027] Compared with the prior art, the present invention has the following advantages:
[0028] The molecular sieve composite material of the present invention is a composite of at least one of SCM-1, SCM-2, and SCM-6 molecular sieves and polyethyleneimine, which can significantly increase the loading amount of polyethyleneimine. When used as a carbon dioxide adsorbent, it can significantly increase the carbon dioxide adsorption amount and has excellent carbon dioxide adsorption and capture capabilities. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 The carbon dioxide gas adsorption and desorption isotherms of the SCM-1 molecular sieve and the obtained molecular sieve composite material at 40° C. in Example 1;
[0030] Figure 2 The carbon dioxide gas adsorption-desorption isotherms of the SCM-2 molecular sieve and the obtained molecular sieve composite material in Examples 5 and 8, and the SBA-15 and the obtained molecular sieve composite material in Comparative Example 3 at 40° C. respectively;
[0031] Figure 3 This is a scanning electron microscope image (SEM) of the molecular sieve composite material obtained in Example 2;
[0032] Figure 4 This is a scanning electron microscope image (SEM) of the molecular sieve composite material obtained in Example 9;
[0033] Figure 5 is the air atmosphere thermogravimetric analysis curve of the molecular sieve composite material obtained in Example 2;
[0034] Figure 6 is the air atmosphere thermogravimetric analysis curve of the molecular sieve composite material obtained in Example 1;
[0035] Figure 7 The graph is a comparison of the CO2 adsorption effects of the molecular sieve composite material obtained in the present invention and other materials loaded with different amounts of PEI. DETAILED DESCRIPTION
[0036] According to the present invention, the molecular sieve composite material obtained above can be used in any physical form, such as powder, granule or molded product (such as strip, clover, etc.). These physical forms can be obtained in any conventional manner known in the art without particular limitation.
[0037] In the context of this specification, including in the following examples and comparative examples, the model of the scanning electron microscope (SEM) of the molecular sieve and its composite material is S-4800II field emission scanning electron microscope.
[0038] In the context of this specification, including the following examples and comparative examples, the thermogravimetric analysis instrument for molecular sieves and their composite materials is a US TA Instrument SDT Q600, and the test is conducted using an air atmosphere at 100 mL / min.
[0039] In the context of this specification, including in the following examples and comparative examples, the specific surface area and pore structure characterization of the molecular sieve and its composite material is measured by nitrogen physical adsorption and desorption method (BET method): the nitrogen adsorption and desorption isotherms of the molecular sieve and its composite material at 77K are measured using an adsorption analyzer (Microtrac BELSORP max II adsorption instrument), and then calculated by the BET equation and t-plot equation; the carbon dioxide adsorption capacity of the molecular sieve and its composite material is characterized by the carbon dioxide gas adsorption and desorption isotherms: measured by the volume method, the carbon dioxide adsorption and desorption isotherms of the molecular sieve and its composite material at 0-40°C are measured using an adsorption analyzer. The experimental conditions for the molecular sieve and its composite material are: the measurement temperature is -169°C (i.e. 77K, the nitrogen adsorption and desorption are tested at the boiling point of liquid nitrogen to use the BET method) or 0-60°C (accurate adjustment can be achieved by water bath circulation temperature control), and the molecular sieve composite material is vacuum pretreated at 100-150°C for 4-6 hours before measurement.
[0040] The present invention is further described in detail below using examples, but the present invention is not limited to these examples.
[0041] Example 1
[0042] 1.00 g of polyethyleneimine (purity 99 wt%, average molecular weight 600) was dissolved in 8 g of anhydrous methanol, stirred to make it uniformly dissolved, and then 1.00 g of calcined SCM-1 molecular sieve powder (prepared in the same manner as in Example I-1 of CN104511271B, with a specific surface area of 524 m 2 / g), stirred to make it completely dispersed and continued to stir in air at 25°C for 24 hours. After completion, it was placed in a vacuum drying oven at 50°C for 6 hours to obtain a molecular sieve composite material. The solvent extracted by vacuum extraction can be recovered and continued to be used as the solvent of the impregnation solution of the present invention.
[0043] Example 2
[0044] 0.4286 g of polyethyleneimine (purity 99 wt%, average molecular weight 600) was dissolved in 5 g of anhydrous methanol, stirred to make it uniformly dissolved, and then 1.00 g of calcined SCM-1 molecular sieve powder (same as Example 1) was added, stirred to make it completely dispersed and stirred continuously for 36 hours in air at 25-30°C. After completion, it was placed in a vacuum drying oven at 55°C for 8 hours to obtain a molecular sieve composite material, and the solvent extracted by vacuum extraction can be recovered and continued to be used as the solvent of the impregnation solution of the present invention.
[0045] Example 3
[0046] 0.6667 g of polyethyleneimine (purity 99 wt%, average molecular weight 600) was dissolved in 4 g of anhydrous ethanol, stirred to make it uniformly dissolved, and then 1.00 g of SCM-2 molecular sieve powder (uncalcined, prepared by the same method as in Example II-2 of CN104511271B, with a specific surface area of 533 m 2 / g), stirred to make it completely dispersed and continued to stir in 20°C air for 48 hours. After completion, it was placed in a vacuum drying oven with ventilation and heat preservation at 50°C for 8 hours to obtain a molecular sieve composite material. The solvent extracted by vacuum extraction can be recovered and continued to be used as the solvent of the impregnation solution of the present invention.
[0047] Example 4
[0048] 0.25 g of polyethyleneimine (purity 99 wt%, average molecular weight 1800) was dissolved in 5 g of anhydrous isopropanol, stirred to make it evenly dissolved, and then 1.00 g of calcined SCM-6 molecular sieve powder (prepared in the same manner as in Example 1 of CN105217651B, with a specific surface area of 394 m 2 / g), stirred to make it completely dispersed and continued stirring for 12 hours in air at 30-35°C. After completion, it was placed in a vacuum drying oven at 50°C for 6 hours to obtain a molecular sieve composite material. The solvent extracted by vacuum extraction can be recovered and continued to be used as the solvent of the impregnation solution of the present invention.
[0049] Example 5
[0050] 0.25 g of polyethyleneimine (purity 99 wt%, average molecular weight 600) was dissolved in a mixed solvent of 3 g of methanol and 2 g of ethanol, stirred to make it uniformly dissolved, and then 1.00 g of the original powder of SCM-2 molecular sieve (same as in Example 3) was added, stirred to make it completely dispersed and stirred continuously in air at 25-30° C. for 24 hours. After completion, it was placed in a vacuum drying oven at 60° C. for 9 hours to obtain a molecular sieve composite material, and the mixed solvent extracted by vacuum extraction can be recovered and continued to be used as the solvent of the impregnation solution of the present invention.
[0051] Example 6
[0052] 2.00 g of polyethyleneimine (purity 99 wt%, average molecular weight 10000) was dissolved in 13 g of methanol, stirred to make it uniformly dissolved, and then 2.00 g of calcined SCM-1 molecular sieve powder (same as Example 1) was added, stirred to make it completely dispersed and stirred continuously in air at 25-30° C. for 48 hours. After completion, it was placed in a vacuum drying oven at 55° C. for 10 hours to obtain a molecular sieve composite material, and the solvent extracted by vacuum extraction can be recovered and continued to be used as the solvent of the impregnation solution of the present invention.
[0053] Example 7
[0054] 8.00 g of 25% aqueous solution of polyethyleneimine (average molecular weight 3000) was dissolved in 8 g of ethanol, stirred to make it uniformly dissolved, and then 2.00 g of SCM-6 molecular sieve raw powder (uncalcined, the preparation method is the same as that of Example 1 of CN105217651B) was added, stirred to make it completely dispersed and stirred continuously in air at 25-30°C for 60 hours. After completion, it was placed in a vacuum drying oven at 60°C for 18 hours to obtain a molecular sieve composite material, and the solvent extracted by vacuum extraction can be recovered and continued to be used as the solvent of the impregnation solution of the present invention.
[0055] Example 8
[0056] 1.00 g of polyethyleneimine (purity 99 wt%, average molecular weight 1800) was dissolved in a mixed solvent of 3 g of methanol and 2 g of ethanol, stirred to make it uniformly dissolved, and then 1.00 g of the original powder of SCM-2 molecular sieve (same as in Example 3) was added, stirred to make it completely dispersed and stirred continuously in air at 25-30° C. for 24 hours. After completion, it was placed in a vacuum drying oven at 60° C. for 12 hours to obtain a molecular sieve composite material, and the mixed solvent extracted by vacuum extraction can be recovered and continued to be used as the solvent of the impregnation solution of the present invention.
[0057] Example 9
[0058] 1.50 g of polyethyleneimine (purity 99 wt%, average molecular weight 1200) was dissolved in a mixed solvent of 4 g of methanol and 2 g of isopropanol, stirred to make it uniformly dissolved, and then 1.00 g of calcined SCM-1 molecular sieve powder (same as in Example 1) was added, stirred to make it completely dispersed and continued to stir in 25°C air for 24 hours. After completion, it was placed in a vacuum drying oven at 60°C for 12 hours to obtain a molecular sieve composite material, and the mixed solvent extracted by vacuum extraction can be recycled and continued to be used as the solvent of the impregnation solution of the present invention.
[0059] Comparative Example 1
[0060] In addition to the impregnation carrier, 1.00 g of 100-200 mesh porous silica (specific surface area of 337 m 2 / g), and the rest is the same as in Example 1.
[0061] Comparative Example 2
[0062] In addition to the impregnation carrier, 1.00 g of 200-300 mesh porous silica (specific surface area of 363 m 2 / g), and the rest is the same as in Example 2.
[0063] Comparative Example 3
[0064] In addition to the impregnation of 1.00 g of SBA-15 mesoporous silica material (specific surface area of 767 m 2 / g), and the rest is the same as in Example 1.
[0065] Comparative Example 4
[0066] 0.6667 g of polyethyleneimine (purity 99 wt%, average molecular weight 600) was dissolved in 5 g of anhydrous methanol, stirred to make it evenly dissolved, and then 1.00 g of calcined MCM-22 molecular sieve powder (specific surface area 430 m 2 / g), stirred to make it completely dispersed and continued to stir in air at 25-30°C for 36 hours. After completion, it was placed in a vacuum drying oven at 55°C for ventilation and heat preservation for 8 hours to obtain a molecular sieve composite material. The solvent extracted by vacuum extraction can be recovered and continued to be used as the solvent of the impregnation solution of the present invention.
[0067] Comparative Example 5
[0068] 1.00 g of polyethyleneimine (purity 99 wt%, average molecular weight 1800) was dissolved in a mixed solvent of 3 g of methanol and 2 g of ethanol, stirred to make the solution uniform, and then 1.00 g of MCM-22 molecular sieve raw powder (uncalcined, specific surface area 386 m 2 / g), stirred to make it completely dispersed and continued to stir in air at 25-30°C for 24 hours. After completion, it was placed in a vacuum drying oven at 60°C for 12 hours to obtain a molecular sieve composite material. The solvent extracted by vacuum extraction can be recovered and continued to be used as the solvent of the impregnation solution of the present invention.
[0069] Table 1 Adsorption performance results of Examples 1 to 9 and Comparative Examples 1 to 5
[0070]
[0071] The above describes the specific implementation of the present invention in detail, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the various technical features being combined in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A molecular sieve composite material, comprising molecular sieve and polyethyleneimine, wherein the molecular sieve is at least one of SCM-1, SCM-2 and SCM-6, and based on the weight of the composite material, the content of polyethyleneimine is 20% to 60%, and the content of the molecular sieve is 40% to 80%.
2. The molecular sieve composite material according to claim 1, characterized in that: Based on the weight of the composite material, the content of polyethyleneimine is 45% to 55%, and the content of molecular sieve is 45% to 55%.
3. The molecular sieve composite material according to claim 1, characterized in that: The specific surface area of the molecular sieve is 30 to 1000 square meters per gram, preferably 150 to 700 square meters per gram; and / or the average molecular weight of the polyethyleneimine is 300 to 100000, preferably 500 to 10000.
4. The method for preparing the molecular sieve composite material according to any one of claims 1 to 3, comprising: (1) dissolving polyethyleneimine in a solvent to prepare an impregnation solution, and then adding a molecular sieve material for impregnation; (2) After impregnation, the product is dried to obtain a molecular sieve composite material.
5. The preparation method according to claim 4, characterized in that: The solvent used in the impregnation liquid is selected from one or more of methanol, ethanol, isopropanol, butanol, cyclohexanol, acetone, water, etc., preferably at least one of methanol, ethanol and water; and / or, in the impregnation liquid, the mass concentration of polyethyleneimine is 0.05% to 30%, preferably 1% to 25%.
6. The preparation method according to claim 4, characterized in that: In step (1), the immersion temperature is 1 to 50° C., preferably 15 to 40° C., more preferably 20 to 30° C.; and / or the immersion time is 3 to 120 hours, preferably 6 to 72 hours.
7. The preparation method according to claim 4, characterized in that: In step (2), the drying temperature is 40 to 150° C., more preferably 50 to 130° C., and the drying time is 2 to 30 hours, preferably 3 to 24 hours.
8. Use of the molecular sieve composite material according to any one of claims 1 to 3 in carbon dioxide adsorption.
9. The use according to claim 8, characterized in that: The application includes: a gas containing carbon dioxide is contacted with the molecular sieve composite material for adsorption to obtain a purified gas; further, in the gas containing carbon dioxide, the volume content of carbon dioxide is 0.04% to 60% by volume, and other gases include at least one of nitrogen, methane, hydrogen, and carbon monoxide.
10. The use according to claim 9, characterized in that: The adsorption conditions are as follows: temperature is 10-80°C, preferably 40-70°C, pressure is 0.01-100 kPa, time is 1-60 min, volume space velocity is 5-2400 h -1 .
Citation Information
Patent Citations
Layered material loaded with polyethyleneimine and its preparation method
CN104437418B
A molecular sieve, its manufacturing method and its application
CN104511271B
SCM-6, aluminosilicate molecular sieve, its synthesis method and applications
CN105217651B
Organic-inorganic composite carbon dioxide adsorbing material and preparation method thereof
CN102500324A
Aluminosilicate molecular sieve SCM-6, and synthetic method and use thereof
CN105217651A